Problems and Priorities of the “Lower Duna” European Region Development Under the European Union Expansion: Array - Merculov, Mykola; Metil, Tatiana (Journal of Danubian Studies and Research, 2020)
It is presented how European integration provides new opportunities for Ukraine and its regions. At the same time, the integration of Ukraine into the European economic space requires the elaboration of its own competitive strategy for each of the cross-border regions, ensuring the formation of appropriate public ideology of their competitiveness. Cross-border cooperation is too slowly adapting to the fundamentally new geo-economic conditions that have emerged since the enlargement of the European Union and the direct approximation of EU borders to Ukraine. The cluster structure of the cross-border region economy – it is ensuring the sustainable development of socio-economic processes and increasing the competitiveness, attractiveness of the region for further investments. Cluster development as a factor of increasing regional competitiveness is a characteristic feature of a modern innovation economy. On the way to Ukraine's accession to the EU, the experience of European cross-border cooperation as a preliminary and complementary stage of regional integration is generalized. The necessity to develop and implement a cross-border strategy for the development of the Euroregions, taking into account the European experience of transregional strategying, which object is the sustainable socio-economic development of the Euroregional system in the unity of its human, natural-resource, production potentials on the basis of network clusters, is presented.